[LiCl2]− Superhalide: A New Charge Carrier for Graphite Cathode of Dual‐Ion Batteries. (4th March 2022) - Kim, Keun‐il; Tang, Longteng; Mirabedini, Pegah; Yokoi, Amika; Muratli, Jesse M.; Guo, Qiubo; Lerner, Michael M.; Gotoh, Kazuma; Greaney, Peter Alex; Fang, Chong; Ji, Xiulei
Abstract: New acceptor‐type graphite intercalation compounds (GICs) offer candidates of cathode materials for dual‐ion batteries (DIBs), where superhalides represent the emerging anion charge carriers for such batteries. Here, the reversible insertion of [LiCl2 ] − into graphite from an aqueous deep eutectic solvent electrolyte of 20 m LiCl + 20 m choline chloride is reported. [LiCl2 ] − is the primary anion species in this electrolyte as revealed by the femtosecond stimulated Raman spectroscopy results, particularly through the rarely observed H–O–H bending mode. The insertion of Li–Cl anionic species is suggested by 7 Li magic angle spinning nuclear magnetic resonance results that describe a unique chemical environment of Li + ions with electron donors around. 2 H nuclear magnetic resonance results suggest that water molecules are co‐inserted into graphite. Density functional theory calculations reveal that the anionic insertion of hydrated [LiCl2 ] − takes place at a lower potential, being more favorable. X‐ray diffraction and the Raman results show that the insertion of [LiCl2 ] − creates turbostratic structure in graphite instead of forming long‐range ordered GICs. The storage of [LiCl2 ] − in graphite as a cathode for DIBs offers a capacity of 114 mAh g −1 that is stable over 440 cycles. Abstract : The reversible storage of the lightest superchloride, [LiCl2 ] −, in graphite cathode of an aqueous dual‐ion battery is reported. Storage of this superchloride in graphite exhibits a reversible capacity of 110 mAh g −1 over 400 cycles. Stimulated Raman, solid‐state nuclear magnetic resonance, and density functional theory calculations reveal that the hydrated [LiCl2 ] − is the charge carrier inserted in graphite.